Water treeing in the solid insulator under ground cable - Tamsir, Tarmidi (Universiti Teknologi Malaysia, 2006)
This study is describes the work carried out the investigation of the problem of water trees in dielectrics used as insulation in high-voltage cables. The investigation covers the design and development of testing technique to examine the more fundamental aspects of water trees. This includes the design of variable high voltage and high frequency power supply, preparation of test samples with water electrodes and observation and measurement of growth of water trees.